2018
DOI: 10.2478/mmcks-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Modeling systems thinking in action among higher education leaders with fuzzy multi-criteria decision making

Abstract: The college and university systems are more complex and required persistent approach towards adoption and transformation. Highly vulnerable environment portrays the need to visualize the regular and strategic issues with the larger perspectives as a whole and develop a model which is more focused towards sustainability and reformation. The current study has attempted to conceptualize systems thinking in action model which consists of four stages of action cycle; diagnosis and analysis, modeling, intervention a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
0
11
0
2
Order By: Relevance
“…The new role of HEIs in social value creation can only be achieved when societal needs can be integrated into HEI activities, and knowledge generated can be used to solve real-life societal challenges. To manage the prevailing challenges and to improve the engagement of HEIs in social innovation practices require an understanding of an integrated approach that leads towards the redesigning and transformation in different levels of processes and functions of HEIs that can improve their capacity for social innovation [6].…”
Section: Introductionmentioning
confidence: 99%
“…The new role of HEIs in social value creation can only be achieved when societal needs can be integrated into HEI activities, and knowledge generated can be used to solve real-life societal challenges. To manage the prevailing challenges and to improve the engagement of HEIs in social innovation practices require an understanding of an integrated approach that leads towards the redesigning and transformation in different levels of processes and functions of HEIs that can improve their capacity for social innovation [6].…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that interviews are transcribed in full, the transcription of each interview was sent to the respective interviewee and was used in the research once it was confirmed by the interviewees. (Ackoff, 2006;Masys, 2016;Shukla, 2018;Siriram, 2020) (c) Application and implementation of research (Masys, 2016;Shukla, 2018;Siriram, 2020) 3. What are your suggestions for improving studies based on systems thinking?…”
Section: Discussionmentioning
confidence: 99%
“…Feedback loops are either reinforcing or balancing (Adam, 2003). Shukla (2018) tried to conceptualize systems thinking in action model, which involves four steps of action cycle including diagnosis and analysis, modelling, intervention and review and lessons learned. These stages create a chain that enables the transformation of theory into practice.…”
Section: Systems Thinking: Concepts and Developmentmentioning
confidence: 99%
See 2 more Smart Citations